PtoMYB031, the R2R3 MYB transcription factor involved in secondary cell wall biosynthesis in poplar - Tang, Feng; Jiao, Bo; Zhang, Meng; He, Minghui; Su, Ruiying; Luo, Keming; Lan, Ting (Frontiers in Plant Science, 2024)
The biosynthesis of the secondary cell wall (SCW) is orchestrated by an intricate hierarchical transcriptional regulatory network. This network is initiated by first-layer master switches, SCW-NAC transcription factors, which in turn activate the second-layer master switches MYBs. Together, these factors stimulate the expression of downstream functional genes and regulate xylem specification and differentiation related to secondary cell wall formation. However, the roles of most MYBs in woody plants are yet to be fully understood. In this study, we have identified and isolated an R2R3-MYB transcription factor, PtoMYB031, from P. tomentosa. This factor predominantly expressed in xylem, acts as a transcriptional repressor and is localized to the nucleus. Overexpression of PtoMYB031 in poplar significantly reduces the content of lignin, cellulose and hemicelluloses. This overexpression also markedly inhibits vascular development in stems, leading to a substantial decrease in SCW thickness in xylem tissues. Our gene expression analyses further demonstrated that most of the structural genes involved in SCW biosynthesis were significantly downregulated in PtoMYB031-OE lines. Conversely, RNA interference of PtoMYB031 lead to an increase in the content of lignin, cellulose and hemicelluloses. Through Yeast two-hybrid (Y2H) and bimolecular fluorescence complementation (BiFC) assays, we discovered that PtoMYB031 can recruit the repressor PtoZAT11 to form a transcriptional inhibition complex. The Effector-Reporter assay further revealed that this PtoMYB031-PtoZAT11 complex can suppress the expressions of master switches, PtoWND1A and PtoWND2B. Our work provides a novel insight into the role of PtoMYB031 in forming a transcriptional inhibition complex to regulate SCW biosynthesis in poplar, and advanced our understanding of this complex process.